The Role of Parents in Increasing Interest in Learning Islamic Religious Education online in High School - Hapida Hapida; Hisban Thaha; Baderiah Baderiah (State Islamic Institute of Palopo, 2022)
This paper is the result of research to determine the role of parents in increasing student interest in learning Islamic religious education online. The results showed that students' interest in learning online in general was still included in the moderate category, meaning that students' interest in learning online in general from all fields of study was still lacking. Furthermore, the results of the analysis of the distribution of questionnaires carried out to find out the role of parents' roles in increasing student interest in learning Islamic religious education online were included in the high category and resulted in the maximum role of parents, students' interest in learning Islamic religious education online was also included in the high category. The obstacles experienced by parents in carrying out their role to increase students' interest in learning Islamic religious education include: 1) Parents' educational background; 2) Parents' economic level; and 3) availability of time. In order to overcome these obstacles, schools, teachers and parents must establish good cooperation. In addition, parents must further improve communication with their children.